Surviving trees of the atomic bombing of Hiroshima: a message of peace from the public libraries and the EC-614 project of the University of Costa Rica - Rodríguez Valerio, Daniela (2024)
The objective of this article is to publicize the social action project EC-614 of the University of Costa Rica “Trees of peace surviving the Hiroshima atomic bomb: Phase 1: establishment of seedlings in Costa Rica”, as well as the impact it has had especially in public libraries and as a contribution to the fulfillment of objective 16, “Peace, justice and solid institutions”, of the United Nations 2030 Agenda. Therefore, a contextualization of libraries as peace-promoting entities is carried out and the project, its genesis and significance are described. Likewise, the conclusions and learning that have been obtained so far with the development of this collaborative project between the School of Biology and the School of Library and Information Sciences of the University of Costa Rica are presented.